2022
DOI: 10.3847/2041-8213/ac6b32
|View full text |Cite
|
Sign up to set email alerts
|

A New Method for Measuring Infrared Band Strengths in H2O Ices: First Results for OCS, H2S, and SO2

Abstract: Infrared (IR) band strengths are needed to extract accurate molecular abundances from astronomical observations of interstellar and solar system ices. However, laboratory measurements of such intensities often have required multiple assumptions about ice composition and thickness. Here we describe a method that circumvents most of the common assumptions and uncertainties in IR band-strength determinations. We have applied the method to measure IR band strengths of OCS, H2S, and SO2 in the absence and presence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…The OCS contamination is apparent from the small band centered at 2045 cm −1 (Ferrante et al 2008) and is likely introduced by the H 2 S source, which lists OCS as a possible contaminant at 0.2% by volume. Despite being fairly dilute, the band strength for the C = O stretch of OCS is comparable to CO 2 (Yarnall & Hudson 2022b), and minimal contamination from this compound is reasonable. Moreover, this feature can be seen in the spectra of mixtures of H 2 S and H 2 O ice throughout the literature, where similar qualities of H 2 S are used (Jiménez-Escobar & Caro 2011; Yarnall & Hudson 2022b).…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…The OCS contamination is apparent from the small band centered at 2045 cm −1 (Ferrante et al 2008) and is likely introduced by the H 2 S source, which lists OCS as a possible contaminant at 0.2% by volume. Despite being fairly dilute, the band strength for the C = O stretch of OCS is comparable to CO 2 (Yarnall & Hudson 2022b), and minimal contamination from this compound is reasonable. Moreover, this feature can be seen in the spectra of mixtures of H 2 S and H 2 O ice throughout the literature, where similar qualities of H 2 S are used (Jiménez-Escobar & Caro 2011; Yarnall & Hudson 2022b).…”
Section: Resultsmentioning
confidence: 93%
“…Despite being fairly dilute, the band strength for the C = O stretch of OCS is comparable to CO 2 (Yarnall & Hudson 2022b), and minimal contamination from this compound is reasonable. Moreover, this feature can be seen in the spectra of mixtures of H 2 S and H 2 O ice throughout the literature, where similar qualities of H 2 S are used (Jiménez-Escobar & Caro 2011; Yarnall & Hudson 2022b). Recent work has demonstrated that OCS can undergo thermal nucleophilic addition in the presence of methylamine (CH 3 NH 2 ; Mahjoub & Hodyss 2018); however, the kinetics of a simple addition reaction between OCS and H 2 O are unfavorable (Ghosh et al 2010).…”
Section: Resultsmentioning
confidence: 93%
“…In this study, we have taken A n to be 7.3 Â 10 À18 and 4.2 Â 10 À17 cm molecule À1 for the n 1 and n 3 modes, respectively; and have taken r to be 1.395 and 1.893 g cm À1 for amorphous and crystalline SO 2 ice, respectively. 56,57 Uncertainties in the calculated column densities (typically AE12.5%) and ice thickness (on the order of AE0.002 mm) were determined through standard propagation-of-error calculations that assumed a 5% measurement error in the value of P and used published uncertainty values for the values of A n and r that were used. 56,57 It should be noted that these values for A n were calculated for amorphous SO 2 ices deposited at 10 K, 56 while the r values for amorphous and crystalline SO 2 were measured for ices deposited at 19 and 85 K, 56,57 respectively.…”
Section: Experimental Methodologymentioning
confidence: 99%
“…56,57 Uncertainties in the calculated column densities (typically ±12.5%) and ice thickness (on the order of ±0.002 μm) were determined through standard propagation-of-error calculations that assumed a 5% measurement error in the value of P and used published uncertainty values for the values of A ν and ρ that were used. 56,57…”
Section: Experimental Methodologymentioning
confidence: 99%
“…For CH 3 CN the value is less than 2% for both sources. The FWHM and band strengths for the pure ices are taken from 62,65,66 .…”
Section: Ocsmentioning
confidence: 99%